Profil Kemampuan Pemecahan Masalah Matematika Siswa Kelas VIII Sekolah Menengah Pertama Ditinjau Dari Gaya Kognitif - Mau, Maria Sensiana; Son, Aloisius Loka; Salsinha, Cecilia Novianti (MATH-EDU: Jurnal Ilmu Pendidikan Matematika, 2023)
This study aims to describe the problem-solving ability profile of junior high school students in class VIII in terms of cognitive styles from Field Independent and Field Dependent cognitive styles. The research method used is descriptive qualitative. This research was conducted in a junior high school in Belu district, in August 2023. The participants in this study were three FD cognitive style students and three FI cognitive style students. The instrument is a set of questions from the problem-solving ability test, the Group Embedded Figure Test, and interviews. The findings show that the profile of students' abilities in solving mathematical problems with the FI cognitive style is categorized as good in understanding the problem, planning the solution, implementing the solution plan, and checking again. Meanwhile, the ability of students with the FD cognitive style is categorized as sufficient at the stage of understanding the problem and planning a solution, and categorized as lacking at the stage of carrying out the settlement plan and looking back.